Plant Community Composition and Biodiversity Patterns in Urban Parks of Portland, Oregon - Talal, Michelle L.; Santelmann, Mary V. (Frontiers in Ecology and Evolution, 2019)
Urban parks are biodiversity hotspots and are integral components of green infrastructure in urban areas. A variety of land use practices and environmental factors affect urban park biodiversity and vegetation structure, composition, and ecological function, but few studies have compared plant taxonomic composition, structural complexity, and species traits across different types of urban green spaces. The purpose of this study was to better understand the relationships between plant community composition, structural patterns, and environmental and species traits by using a standardized data collection method across different types of urban parks in Portland, Oregon. We examined the potential ways that different types of urban parks preserve native species and/or harbor non-native and invasive species. We used a stratified random sampling design to select 15 parks of different types based on use: 1) recreational-active use parks, 2) natural-passive use parks, and 3) multi-use parks. We found a total of 178 plant species belonging to 141 genera and 65 families. Multivariate analyses, including ordination with non-metric multidimensional scaling and cluster analysis were used to explore vegetation composition data and associations of different species assemblages with environmental variables. One-way analysis of variance was used to test hypotheses about variables associated with diversity. Statistically-significant differences in species richness and biodiversity indices were found between different park types. More native species were found in natural-passive use parks than other park types, more non-native species are found in multi-use parks than the other park types, and more invasive species were found in natural passive-use parks than in recreational-active use parks. Attributes such as natural-passive use park type, wetland habitat, steep slopes, native species origin, non-native species origin, and vine and tree plant forms were those most strongly correlated with the non-metric multidimensional scaling ordination, indicating that these attributes exert the strongest influence on species abundance and distribution with Portland’s urban parks. The findings of this study can assist park managers in their aims to promote native species cover, reduce invasive species presence, or achieve additional management goals for urban parks.